Family Support and Client's Ability to Control Hallucinations: A Cross-Sectional Study - Haruddin, Nurul Azmi; Suhermi; Hidayat, Rahmat (Omni Nursing Journal, 2025)
Background: The high number of hallucinations encourages individuals to be able to recognize hallucination symptoms so that early detection can be known immediately, one of the factors that can create individual coping with hallucinations is the support of family, so the family should be more involved in every nursing action for mental disorders. Objective: The purpose of the study was to determine the relationship between family support and the client's ability to control hallucinations in the Work Area of the Minasatene Health Center, Pangkajene Regency and the Islands in 2024. Methods: This study used an analytical descriptive design with a cross sectional study approach. Results: The results of this study show that there are less than 18 clients who have family support, of which 72.2% are unable to control hallucinations and 27.8% are able to control hallucinations, while clients who have family support are quite 28 clients, of which there are 25.0% who are unable to control hallucinations and 75.0% who are able to control hallucinations. The results of the statistical test with Chi-square obtained a value of ρ=0.004. Conclusion: The conclusion in this study is that there is a relationship between family support and the client's ability to control hallucinations in the Minasatene Health Center Working Area of Pangkajene and Islands Regency in 2021. For this reason, it is hoped that the patient's family needs to increase their concern in providing positive and consistent support to clients to carry out intense control.